Covid-19 for Crowdfunding: Catalyst or Deterrent? Evidence from Russia - Torkanovskiy, Evgeny; Voinov, Alexander (The Indonesian Capital Market Review, 2022)
This paper explores the impact of the COVID-19 pandemic on crowdfunding by analyzing a 2-year sample of 7,024 rewards-based crowdfunding campaigns on the two major Russian platforms. The study employs a digital methods approach to demand and supply and multiple regression analysis. The findings show that COVID-19 and the associated lockdown had no immediate and straightforward effect on the crowdfunding sector, neither on backers nor on campaigns’ initiators. Thus, the crowdfunding sector unlike some other investment classes remains resilient to the global pandemic. Beyond that, empirical analysis revealed the undescribed phenomenon of sponsors’ readiness to finance projects being highly seasonal and depending on the month in which the project starts. The nearer to year end, the more backers are willing to put into crowdfunding projects